Cardioprotective Effects of Paricalcitol Alone and in Combination With FGF23 Receptor Inhibition in Chronic Renal Failure: Experimental and Clinical Studies. (17th October 2018) - Czaya, Brian; Seeherunvong, Wacharee; Singh, Saurav; Yanucil, Christopher; Ruiz, Phillip; Quiroz, Yasmir; Grabner, Alexander; Katsoufis, Chryso; Swaminathan, Sethuraman; Abitbol, Carolyn; Rodriguez-Iturbe, Bernardo; Faul, Christian; et al.
Abstract: BACKGROUND: In uremic animals, vitamin D receptor (VDR) agonists like paricalcitol (Pc) attenuate cardiac hypertrophy, but this effect has not been replicated consistently in humans with chronic kidney disease. Elevated fibroblast growth factor 23 (FGF23) levels cause cardiac hypertrophy with activation of the myocardial calcineurin/nuclear factor of activated T cell (NFAT) axis and may antagonize the cardioprotective effects of VDR agonist therapy. We hypothesized that the effectiveness of Pc may depend on the prevailing circulating levels of FGF23 and could be potentiated by the combined administration of a pan-FGF23 receptor (FGFR) blocker agent (PD173074). METHODS: In rats with 5/6 nephrectomy treated with Pc or PD173074 or both agents concurrently, myocardial mRNA expression of renin–angiotensin system, VDR, FGFR4, and calcineurin/NFAT target genes was determined. In adolescents on hemodialysis, we analyzed sequential echocardiograms, blood pressures and serial FGF23 measurements, and their relations to the cumulative administered dose of parenteral Pc. RESULTS: The ratio of Pc dose/plasma levels of FGF23 correlated inversely ( P < 0.005) with the cardiac mass in uremic rats and in hemodialysis patients, independently of hypertension. Despite persistently elevated FGF23 levels and myocardial FGFR4 activation, Pc suppressed upregulated myocardial calcineurin/NFAT target genes, and the effects were amplified by coadministration of PD173074. CONCLUSIONS: The beneficial effects of Pc on uremic cardiac hypertrophy are counterbalanced by the increased FGF23 levels. Blockade of FGF23-mediated signaling increased the Pc-induced suppression of the myocardial calcineurin/NFAT system. Higher doses of Pc should be considered in the treatment of patients with uremic cardiomyopathy.